The Relation between Central Bank Independence and Inflation Rate in Egypt: An Empirical Analysis during 1998-2019 - ElHodaiby, Mai Wagdy; Elsamman, Ahmed (International Journal of Economics and Financial Issues, 2021)
This paper examines the relation between granting central banks more independence represented in both its manifested legal charter as well as actual practices adopted and inflation in Egypt during the period from 1998-2019. To do so, this paper first looks at the evolution of different central bank independence (CBI) measures and adopts the most comprehensive relevant one. Consequently, it runs a regression model adopting an autoregressive distributed lag (ARDL) model, regressing the dependent variable inflation on its determinants of legal CBI, actual CBI, M2 and openness, to capture such relation in both the short and long term time dimensions in the case of Egypt. The paper further provides an interpretation of computed outcomes, where it presents robust evidence of an inverse relation between inflation and CBI in Egypt in the period under study in its legal and actual form and in both the short-run and the long-run. Keywords: Central bank independence, Central Bank of Egypt, Inflation, Autoregressive distributed lag, unit root test JEL Classifications: E31, E42, E58, E370 DOI: https://doi.org/10.32479/ijefi.10941